Analysis of Knowledge Management in the Context of Projects in Colombia: Subject Area: (Knowledge Management and Project Management) - Rincón-González, César; Díaz Piraquive, Flor Nancy; González-Crespo, Rubén (Springer Science and Business Media Deutschland GmbH, 2022)
This research work conducted a meticulous analysis about the Knowledge Management (KM) in the context of projects in Colombia, with the aim of determinate the way organizations carryout related activities and practices about the matter of study. 3 distinctive KM clusters were identified by conducting an extensive fieldwork and deploying a meticulous statistical analysis of the collected data. Firstly; a theoretical framework was built, allowing the identification of concepts about knowledge management. Secondly; a research methodology was constructed, variables of study were identified and integrated into an information gathering instrument, applied randomly on an extensive fieldwork covering more than 500 organizations nationwide, by interviewing project representatives. Subsequently; a detailed statistical analysis was carryout, techniques such as hierarchical clustering, variables factor maps, Principal Components Analysis (PCA), boxplots and Anova tests, were used to identify the KM clusters related to the management of projects in Colombia. Afterwards; the characteristics of each of the clusters of KM in the context of projects in Colombia were documented. And finally; conclusions were established and as future lines of research were outlined.
Keywords: Colombia; impact analysis; knowledge management; project management; Scopus(2)